The Activity and Ranging Patterns of Gelada Monkeys as Behavioral Responses to the Effects of Livestock Grazing in the Simien Mountains National Park, Ethiopia - Abebe, Belayneh; Ashagrie, Mezgebu; Moges, Eshetu (International Journal of Zoology, 2022)
Understanding of behavioral ecology of primates in grazed lands is vital to their conservation and monitoring strategies. Here we investigated how livestock grazing within the Simien Mountains National Park affects the activity time budgeting and ranging behavior of the geladas, a monkey endemic to Ethiopian highlands. This study was carried out from February 2019 to July 2019 by stratifying the study area as grazed and nongrazed sites. Activity time pattern data were collected using 5 minutes instantaneous scan sampling within 15 minutes intervals from 7:00 to 18:00 for 10 days per month in the grazed and nongrazed sites. The ranging data were also collected by tracking the study group and recording GPS points every 15 minutes sample. The effects of livestock grazing on activity time budgets were statistically analyzed by multiple analyses of variance (MANOVA). Daily range length and home range size were estimated by employing the Open Jump toolbox (MOVEAN), and statistically tested by Mann–Whitney U test. From 3427 behavioral scans on the various activities, feeding was the most frequent (43.04%) behavioral activity followed by moving, accounting for 38.06% of the time. The study revealed that grazing has a statistically significant effect on moving and social activity time budgets. The geladas dwelling in the grazed areas of the park spent more time in moving than in the nongrazed areas. The effect of grazing on social behavior is the reverse of moving. Similarly, geladas traveled longer daily range length and cover a wider home range size in the grazed areas. Therefore, these findings of the study imply that livestock grazing is adversely affecting the behavior of gelada monkeys in the park. To minimize such effects on gelada monkeys and harmonize grazing with wildlife habitat conservation, the grazing pressure reduction strategy must be closely monitored and supported by animal feed cultivation technology.